New species of the Madagascan genus Hovops Benoit, 1968 (Araneae: Selenopidae), with a description of the H. madagascariensis male and an identification key - Corronca, Jose Antonio (2011)
Hovops Benoit is a heterogeneous genus of selenopid spiders represented by six known species endemic to Madagascar. After examining sizeable collections of Selenopidae from the Afrotropical Region especially, from Madagascar, we here propose new diagnostic characters for Hovops and describe three new species: H. betsileo sp. n. (both sexes) from Toamasina Province, H. lidiae sp. n. (both sexes) from Fianarantsoa Province, and H. merina sp. n. (female only) from Antananarivo Province. The male of H. madagascariensis (Vinson) is described for the first time, and new records of this species are also provided. An identification key to the species in this genus is proposed.